A study on the effects of the Qihuang Needle therapy on patients with Parkinson's disease - Li, Xinyu; Zhou, Jingpei; He, Renxiu; Lian, Jiahui; Jia, Jie; Hsu, Chialin; Yuan, Shihua; Chen, Zhenhu (Frontiers in Neurology, 2023)
Objective This study aimed to evaluate the effectiveness of the Qihuang Needle (QHN) in treating Parkinson's disease (PD). Design, setting, and participants The trial was an 8-week randomized clinical trial (4 weeks of treatment followed by 4 weeks of follow-up) conducted from January 2021 to July 2022 in outpatient settings at three clinical sites in Guangzhou, China. Thirty-four participants with PD were diagnosed based on the diagnostic criteria formulated by the brain bank of the British Parkinson's Disease Society in 1992. Interventions Patients in the treatment and control groups received six sessions within 4 weeks of the QHN therapy or the sham acupuncture therapy (two times per week for the first two consecutive weeks and one time per week for the following two consecutive weeks). Main outcomes and measures The primary outcome measure was the change in the Parkinson's Disease Rating Scale-Part III Motor Examination (UPDRS III) between baseline and 8 weeks after treatments. Secondary outcome measures were the Non-Motor Symptoms Scale for Parkinson's Disease (NMSS) and Parkinson's Disease Daily Quality of Life-39 (PDQ-39). Real-time shear wave elastography (SWE) was assessed for each patient at baseline and during the 4-week period as the third outcome measure. Results A more significant reduction of UPDRS III score, PDQ-39, NMSS, and SWE was observed in the QHN group than in the sham acupuncture group. Conclusions The QHN therapy consistently demonstrated superiority and produced clinically meaningful benefits in reducing motor and non-motor symptoms, as well as significantly improving muscle stiffness, in patients with PD.